2011
DOI: 10.1111/j.1834-7819.2011.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe adverse reactions to dental local anaesthetics: systemic reactions

Abstract: Background: Occasionally, patients suffer systemic adverse effects from injections of local anaesthetic solutions. This may range from minor transient vasovagal attacks to life-threatening collapse. Methods: The suspected adverse reactions reported to the Office of Product Review of the Therapeutic Goods Administration (TGA) were analysed in detail.Results: There was a high incidence (70%) of adverse reactions associated with prilocaine, which is much greater than its market share (less than 20%). There is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 17 publications
1
37
0
3
Order By: Relevance
“…The usage of prilocaine has recently decreased and articaine increased. 2 Mepivocaine and bupivacaine are grouped, as not widely used in general dental practice. 19 A recent study based on voluntary reports in Ontario, Canada showed different incidence figures for different types of LA agents with 1 in 332 000 for prilocaine, 1 in 410 000 for articaine and 1 in 2 580 000 for lignocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usage of prilocaine has recently decreased and articaine increased. 2 Mepivocaine and bupivacaine are grouped, as not widely used in general dental practice. 19 A recent study based on voluntary reports in Ontario, Canada showed different incidence figures for different types of LA agents with 1 in 332 000 for prilocaine, 1 in 410 000 for articaine and 1 in 2 580 000 for lignocaine.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, there may be systemic adverse reactions ranging from briefly feeling unwell to total collapse, which is reviewed separately. 2 A different group of adverse reactions to LA injection is when the loss of sensation is prolonged. This may be temporary, where after a few days, weeks or months, sensation returns, or it may be permanent.…”
Section: Introductionmentioning
confidence: 99%
“…The literature includes reports of local and/or systemic alterations that range from the most common situations, like hematomas and fainting, to rarer situations like methehemoglobinemia, allergic reactions, and toxic reactions, even resulting in death 17,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the article by Sambrook et al, 1 articaine is wrongly blamed to be a risk factor for methaemoglobinaemia in humans. In the article by Wilburn-Goo and Lloyd, 2 cited as reference 18 by Sambrook et al, articaine is not even mentioned at all.…”
Section: Severe Adverse Reactions To Dental Local Anaestheticsmentioning
confidence: 99%